Effects of Tissue Flossing on Athletic Performance Measures: A Systematic Review - Scott W. Cheatham; Justin Nadeau; William Jackson; Russell Baker (Sports)
The primary aim of this study was to investigate the efficacy of tissue flossing on athletic performance measures. A secondary aim was to explore the efficacy of tissue flossing when applied to a joint or soft tissue (i.e., muscle belly) on athletic performance measures. An article search was completed in the PubMed/MEDLINE, EBSCO, SCOPUS, and OneSearch electronic databases up to May 2024. Studies were included if they used tissue flossing as a primary intervention among healthy participants and used one or more athletic performance measures as an outcome. Exclusion criteria included studies that did not investigate tissue flossing on athletic performance measures among healthy participants, studies that used tissue flossing for blood flow restriction training, case studies, narrative reviews, dissertations, conference proceedings, and papers written in a language other than English. Eighteen articles and 559 total participants were included in the final analysis. Study quality was assessed by two independent reviewers using the Downs and Black Checklist and the Oxford Centre for Evidence-based Medicine. The major findings suggest that a single tissue flossing treatment ranging from 2 to 10 min that includes active single joint or active closed chain exercises may enhance post-intervention muscle strength, jump performance, and balance up to 45 to 60 min post-intervention. Tissue flossing to a joint or soft tissue both produced mixed results among studies, a definitive answer on which technique is superior cannot be determined at this time. Further direct comparison studies are needed for these two techniques.